The Life Style amongst Nomadic Tribes of Ivan Kalhor, Iran - Aida Mehrad Mehrad; Mahmoud Riyahi (Universitas Ahmad Dahlan, 2017)
AbstractÂ Cooperation is one of the main factors amongst nomadic tribes that caused of their unity and growth; also, it has been determined their life style. Furthermore, the goal of the current literature review was to explain the role of cooperation amongst people of tribes in Ivan Kalhor, Iran; also, illustrated the importance of this humanity factor in views of various famous scientists in the world that determined based on qualitative method. Lack of consideration to some factors such as cooperation in this kind of societies creates the different type of problems, and it can be harmful to nomadic tribes; additionally, it can decrease this population. In another word, the existence of cooperation as one of the principle human needs can advance and support activity and relation of people in tribes and conduct their activity in the correct way. Overall, this literature review that organized by qualitative method (observation and interview) considered to the vital role of cooperation at nomadic tribes in Iran especially in Ivan Kalhor area, and likewise, described its effectiveness on people relationships.Â Keyword: Nomadic Tribes, Cooperation, Ivan Kalhor, IranÂ